Novel noninvasive embryo selection algorithm combining time-lapse morphokinetics and oxidative status of the spent embryo culture medium - Alegre, Lucía; Del Gallego, Raquel; Arrones, Sarai; Hernández, Purificación; Muñoz, Manuel; Meseguer, Marcos (Fertility and sterility, 2019)
To develop a noninvasive embryo selection algorithm consisting of time-lapse morphokinetics and the oxidative status of the spent embryo culture medium determined using the Thermochemiluminescence (TCL) Analyzer. Retrospective cohort. Not applicable. From women participating in the oocyte donation program, data from 505 samples of spent embryo culture media samples from 292 intracytoplasmic sperm injection cycles. None. Morphokinetic parameters assessed during incubation in the time-lapse system Embryoscope. Oxidative parameters (H1 , H2 , and H3 ) from the spent culture medium on day 5 of incubation measured using the TCL assay; and a combined assessment algorithm, including morphology, morphokinetics, and the embryo's culture medium oxidative status, developed as a tool for embryo selection, based on implantation success and confirmed ongoing pregnancy. The levels of the oxidative parameters H1 , H2 , and H3 on day 5 of incubation were statistically significantly higher in transferred and vitrified embryos compared with discarded embryos and in successfully implanted embryos compared with those that did not result in pregnancy. The assessment algorithm resulted in a hierarchical classification with six embryo quality categories (A to F), associated with implantation rates of between 76.5% and 29.2%. An assessment algorithm combining morphology, morphokinetics and the embryo's culture medium oxidative status may help to improve current embryo selection methods criteria and in vitro fertilization success.